The law of global digitality - Kettemann, Matthias C.; Peukert, Alexander, 1973-; Spiecker genannt Döhmann, Indra, 1970- (Routledge research in the law of emerging technologies., 2022)
"The Internet is not an unchartered territory. On the Internet, norms matter. They interact, regulate, are contested and legitimated by multiple actors. But are they diverse and unstructured, or are they part of a recognizable order? And if the latter, what does this order look like? This collected volume explores these key questions while providing new perspectives on the role of law in times of digitality. The book compares six different areas of law that have been particularly exposed to global digitality, namely laws regulating consumer contracts, data protection, the media, financial markets, criminal activity, and intellectual property law. By comparing how these very different areas of law have evolved with regard to cross-border online situations, the work considers whether cyberlaw is little more than "the law of the horse", or whether the law of global digitality is indeed special and, if so, what its characteristics across various areas of law are. The book brings together legal academics with expertise in how law has both reacted to and shaped cross-border, global Internet communication and their contributions consider whether it is possible to identify a particular mediality of law in the digital age. Examining whether a global law of digitality has truly emerged, this book will appeal to academics, students and practitioners of law examining the future of the law of digitality as it intersects with traditional categories of law"--